Image Deformation Based on Wavelet Filter and Control Curves - Hong-an Li; Jie Zhang; Baosheng Kang (Institute of Advanced Engineering and Science, 2014)
We provide an image deformation method based on wavelet filter using control curves and moving least squares. The image is preprocessed firstly instead of being directly deformed by the old ways. And the original image will be filtered into a high frequency part and a low frequency part by the wavelet, and then use the moving least squares and the control curves only to deform the low frequency part, but not the high frequency part. The key points are set to create control curves according to shape information or deformation requirement, and moved to new position to deform the image using moving least squares. The final result of image deformation is obtained by adding the deformed low frequency part to the high frequency part of the original image. Experiments show that the high frequency detail information is well preserved and the image shape and contour are also well described, and so the deformation results are satisfactory and realistic. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4390